2021
DOI: 10.3390/antiox10030403
|View full text |Cite
|
Sign up to set email alerts
|

Protective Activity and Underlying Mechanism of Ginseng Seeds against UVB-Induced Damage in Human Fibroblasts

Abstract: Ginseng seeds are rich in phytosterols, ginsenosides, and fatty acids, and can therefore be used in skincare to delay the aging process. Ginseng seed embryo (GSE) and ginseng seed coat (GSC) were separated from ginseng seeds (Panax ginseng Meyer). This study evaluated the protective activity and underlying mechanism of GSE and GSC on UVB irradiation-induced skin photoaging using Hs68 cells. Their bioactive compounds, including phytosterols, ginsenosides, tocopherols, tocotrienols, and fatty acids were determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…The activated AP-1 acts as a nuclear transcription factor and binds to the promoter of MMPs to induce MMP gene transcription [ 35 ]. Heo and Lee et al [ 36 ] found that the treatment of Hs68 cells with ginseng seed extract attenuated the UV-induced MMP-1 and MMP-3 increments through the MAPK signaling pathway to decrease collagen degradation. Since the primary function of MMPs is to degrade ECM, Col I degradation is initiated by MMP-1 and continued by MMP-3 [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The activated AP-1 acts as a nuclear transcription factor and binds to the promoter of MMPs to induce MMP gene transcription [ 35 ]. Heo and Lee et al [ 36 ] found that the treatment of Hs68 cells with ginseng seed extract attenuated the UV-induced MMP-1 and MMP-3 increments through the MAPK signaling pathway to decrease collagen degradation. Since the primary function of MMPs is to degrade ECM, Col I degradation is initiated by MMP-1 and continued by MMP-3 [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the larger amount of pro-collagen attained by phytonutrient and estradiol treatments, and the reduced level of MMP-1, can restore this balance and, thus, improve skin elasticity. Previous studies have shown that polyphenols reduce MMP expression, both in vivo [ 43 ] and in vitro [ 17 ]. A similar reduction in MMP expression was shown by carotenoids in dermal fibroblasts [ 44 ] and in human skin [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that the protective effects of phytonutrients are mediated by the modulation of signaling pathways that are involved in the adverse effects of oxidative stress. This modulation includes reduction in the activities of the nuclear factor-κB (NF-κB) transcription system, activator protein 1 (AP-1), and mitogen-activated protein kinase (MAPK) [ 17 , 18 ], and improving the antioxidant defense mechanism [ 19 ]. Several studies, including our own, suggest that modulation of these signaling pathways by phytonutrients can lead to a reduction in inflammatory processes [ 20 , 21 , 22 ] and MMP expression [ 17 , 23 ], and increase collagen synthesis [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Autophagic death represents an important and dynamic cellular event in which unwanted and impaired organelles/proteins are degraded 3 . Dermal fibroblasts biosynthesize collagen and perform extracellular matrix (ECM) remodeling 4 . The latter cells have critical functions in photoaging and anti‐aging, particularly in case of skin exposure to cumulative damage by ultraviolet exposure.…”
Section: Introductionmentioning
confidence: 99%
“…3 Dermal fibroblasts biosynthesize collagen and perform extracellular matrix (ECM) remodeling. 4 The latter cells have critical functions in photoaging and anti-aging, particularly in case…”
mentioning
confidence: 99%